Peran Pendidikan Agama Islam dalam Membangun Kecerdasan Spritual Peserta Didik di MTs Darul Ishlah Lendang Batah Lombok Tengah - muaini, muaini (LP2M STAI Darul Kamal NW Kembang Kerang, 2025)
This research aims to examine the role of Islamic Religious Education (PAI) in developing students' spiritual intelligence at MTs Darul Ishlah Lendang Batah, Praya. Islamic Religious Education is a vital instrument in shaping students' character and spiritual values. This study employs a qualitative approach with a case study method, where data are obtained through observations, interviews, and documentation. The research subjects consist of PAI teachers, the school principal, and students.The results show that PAI significantly contributes to enhancing students' spiritual intelligence through the integration of Islamic values into learning activities. The implemented learning processes include activities such as practicing congregational prayers, reciting the Qur'an, discussing moral values, and reinforcing noble character. Furthermore, the role of teachers as role models in providing motivation and spiritual guidance greatly influences the character development of students. However, there are challenges in its implementation, such as the lack of support from family environments and diverse societal conditions.Nevertheless, collaborative efforts between schools, parents, and the community can serve as a solution to these challenges. This research concludes that Islamic Religious Education at MTs Darul Ishlah Lendang Batah effectively develops students' spiritual intelligence through a holistic and contextual approach.